Rural communities are more physically active in Indonesia: the results on Indonesian national survey data - Wildan Haru Pradani; Anindra Guspa; Amin Akbar; Izzanil Hidayati; Wirza Feny Rahayu; Putri Sukma Deri; Fidia Oktarisa (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Physical activity is an important component of maintaining physical and mental health, including reducing the risk of chronic diseases and improving cognitive function. However, nearly a quarter of the global adult population is physically inactive, with factors such as geographic location (urban vs. rural) and socioeconomic conditions influencing participation levels.